Trans-Pacific partnership: A challenge to Europe - Matthias Bauer; Fredrik Erixon; Martina Ferracane; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2014)
What if the Trans-Pacific Partnership (TPP) is not a doomed initiative - and what if it will actually make inroads into modern trade problems? The Asia-Pacific region is now the world's centre of economic gravity holding an increasing share of world production and promising a rapid turn into the world's fastest growing consumer market. TPP will change the competitive relation between European and American firms as far as access to this market is concerned. The negotiations now include Australia, Brunei, Canada, Chile, Japan, Malaysia, Mexico, New Zealand, Peru, Singapore, the US, and Vietnam. Influential actors, including South Korea, Philippines, Taiwan, Thailand, (and even China) have formally or informally shown their interest in joining the negotiations. There is no reason to doubt that TPP is the new agenda-setting pillar in the Asia-Pacific region and beyond representing 60% of world trade - the same level as GATT during the 1980s. (...)
Keywords: 330; Wirtschaftsintegration; Asiatisch-pazifischer Raum; Verhandlungen